Performance appraisal System an effective performance management system: Perceptions of employees at Mashwede Holdings. - Nyasha, Mapira (IJRDO - Journal of Applied Management Science, 2016)
The research sought to assess perceptions of employees on the effectiveness of performanceappraisal as a performance management tool at Mashwede Holdings in Zimbabwe. The researchwas carried out in the form of a case study in which a sample of 52 employees from a populationof 74 employees was used. Stratified random sampling procedure was employed in selectingelements from 6 managers and 46 general employees. Questionnaires and interviews were usedin triangulation to collect data on the sample. After analyzing the collected data, it was found thatperformance appraisal assist in performance measurement. The study also found that theeffectiveness of performance appraisal system is a cause of concern because of its shortfalls. Theeffectiveness of performance appraisal system has been hampered by various challenges such ashalo effect, horn effect, stiffness, central tendency and personal bias. The study recommendedthat modern methods of performance appraisal be used and make use of contemporaryperformance management systems like Results Based Management (RBM) and Balance ScoreCard system (BSC).